Attributes of Private Pharmacy School Graduates as Care Providers: A Cross-sectional Study from Saudi Arabia - Alqifari, Saleh Fahad (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: This study aimed to measure the level of preparedness of recent pharmacy program graduates to deliver patient care. Materials and Methods: A cross-sectional study was conducted using a validated self-administered online survey. Intended outcome measures of the survey instrument include the perception of 46 graduates regarding 16 patient care attributes. Results: Most graduates believe that they acquired the attributes named in this study. Gender appeared to not influence graduates’ belief in the possession of attributes of interest. Graduates working in the private sector or currently seeking employment reported less confidence in possession of attributes related to “self-awareness”, “self-learning”, “self-audit”, “excitement towards pharmacy subjects”, “tolerance of uncertainty” and “compassion’’. Conclusion: Results suggest that pharmacy curricula provided adequate support for graduates’ confidence to provide patient care with equal harmony between male and female campuses. Moreover, government employment installed higher confidence in pharmacy graduates compared to the private sector.
Keywords: Patient care; Pharmacist attitude; Pharmacy education; Pharmacy graduates; Care provider; Pharmacist attributes